Two new species of Fistulina (Agaricales, Basidiomycota) from the Northern Hemisphere - Zhou, Meng; Liu, Zhan-Bo; Lim, Young Woon; Cho, Yoonhee; Yang, Rui-Heng; Bao, Da-Peng; Zhao, Chang-Lin; Li, De-Wei; Vlasák, Josef; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Phylogenetic and morphological analysis on samples of Fistulina from East Asia and North America were carried out, and two new species were described: Fistulina americana and F. orientalis, both previously known as Fistulina hepatica. The former is characterized by lateral stipitate basidiocarps, relatively small pores (7–8 per mm), a monomitic hyphal system with both clamp connections and simple septa, ellipsoid basidiospores of 4–4.8 × 3–3.3 µm; the species has been found on Quercus in North-East USA. F. orientalis is characterized by lateral stipitate basidiocarps, very small pores (11–12 per mm) with pruinose dissepiments, a monomitic hyphal system with both clamp connections and simple septa, ovoid to subglobose basidiospores of 3–4 × 2.7–3 µm; the species has been found on Castanopsis in East Asia. Phylogenetically, samples of Fistulina americana and F. orientalis form two new lineages nested in the Fistulina clade.